Systematic Review of Literature Applied to the Jesuit Landscape of the Municipality of Uruguaiana, RS - Morari, Mariana Nicorena; Weiss, Raquel; Pippi, Luis Guilherme Aita (National Journal of City Management, 2022)
The Jesuit missions were of fundamental importance during the colonization period, with the proposal to catechize and protect the local indigenous from the slavery imposed by the Bandeirantes. The Jesuit priests developed a system of reductions, villages that had urban and rural structures, to self-support, helping each other in times of need. The Yapeyú Smelter, located on land now belonging to Argentina, would have been the most populous of the reductions and had the largest Jesuit cattle ranch, located on the opposite bank of the Uruguay River, in what is now Brazilian territory, the municipality of Uruguaiana/RS. Through the structure of their ranch, the Jesuits created their own landscape, which possibly would have influenced the formation of the local identity, with cattle raising still being the main economic base of the municipality. The article aimed to understand the state of art referring to scientific research on the Jesuit landscape in Uruguaiana or even in Rio Grande do Sul. For this, the systematic literature review method was used, which, through protocols for the development of the research, gathered materials that were grouped and evaluated, through bibliometric analysis.